Opioid use in pediatric otolaryngologic surgery: A survey of caregivers' attitudes - Ward, MA, Libby M.; LaRosa, BS, Allyson H.; Prakash, BA, Yash; Cohen, MD, Michael B.; Levi, MD, Jessica R. (Journal of Opioid Management, 2022)
Objective: Given the current opioid epidemic and the fact that children continue to be undertreated for pain following surgeries, it is important to understand caregivers’ attitudes toward post-operative opioid use. Design: A survey was distributed to caregivers of pediatric patients undergoing otolaryngologic procedures. Setting: An academic hospital in Boston, Massachusetts. Participants: Sixty-eight caregivers completed the survey. Main outcome measure: Caregiver attitudes toward post-operative opioid use. Results: The study results are as follows: 38.1 percent of parents stated they would feel comfortable giving their child opioids post-operatively, 30.2 percent would not feel comfortable, and 31.7 percent were unsure. For every increase in 1 year of age of the child, there was an increase in the odds of a parent being comfortable giving opioids. Caregivers who had taken opioids in the past were more likely to feel comfortable, while those who were employed were less likely to feel comfortable. The most common reason reported for not feeling comfortable was addiction potential. The comfort level did not differ based on the caregivers’ education level, income, race, or language. Conclusion: The majority of caregivers are unsure about or do not feel comfortable giving their child opioids post-operatively. Most are specifically concerned about the risk of addiction. Understanding caregivers’ views on opioids in a diverse patient population is essential, so surgeons can counsel caregivers and provide appropriate post-operative pain management in their patients.